A Tribute to Bentzi Karsh: His Contributions to Macroergonomics in Health Care Research and Education. (September 2013) - Carayon, Pascale; Kleiner, Brian; Robertson, Michelle; Weinger, Matt; Wetterneck, Tosha; Holden, Rich; Rodriguez, Joy; Montague, Enid
The objective of this session is to display the range of contributions to human factors research and education by Professor Bentzi Karsh who passed away too early in August 2012. The session will consist of a series of presentations by colleagues and students of Professor Karsh to highlight his deep and broad contributions.